PELATIHAN SIMULATOR APLIKASI SMARTCLASS ROOM BERBASIS IoT UNTUK GURU- GURU SMK NASIONAL BANDUNG - Prajna Deshanta Ibnugraha; Muhammad Ikhsan Sani; Nina Hendrarini; Ema ema (Politeknik Caltex Riau, 2024)
Revitalization of vocational schools is the core of the mandate of Presidential Instruction No. 9/2016 on Revitalization of Vocational High Schools (SMK). Vocational Education is education that refers to the mastery of applied expertise in a particular field. Students will be equipped with theory and also the implementation of learning in the form of practice. The Ministry of Education and Culture adjusts and develops the vocational education curriculum and adjusts it to be demand-driven so that the business world and the industrial world (DUDI) are more actively involved in the vocational education process in SMK. This IoT-based Smart class Room Application Simulator abdimas program aims to provide insight and increase competence for SMK teachers so that they can work and implement this knowledge to their students. The results of this abdimas feedback are 60% agree and 40% strongly agree. This shows that this abdimas program has succeeded in providing benefits to SMK teachers.